TRENDS AND KNOWLEDGE STRUCTURE IN GLOBAL STUDIES OF EDUCATION AND SOCIAL TRANSFORMATION: A BIBLIOMETRIC ANALYSIS (2000–2024) - Imanulyaqin, Muhammad Nur; Wahyuni, Fauziah Sri; Utami, Patrisia Rahayu; Ramadhan, Iwan (Universitas Labuhanbatu, 2025)
Purpose–Education functions not only as an instrument for advancing social transformation toward improved quality of life but also as a medium for preserving cultural identity amid global modernization. Despite the growing attention to these themes, no prior bibliometric study has systematically mapped the intellectual structure and global development of research on the connections between education and social transformation. Filling this gap, the article conducts a systematic bibliometric comparison of documents indexed in Scopus between 2000 and 2014, encompassing both journal articles and conference papers.Methodology–The study constructs the knowledge structure based on VOSviewer and explores trends in publications, influential authors, core journals, contributing countries, and frontier research in this field. Five publication phases were identified: the early, slower-growth phase (2000–2005), the period of fluctuating expansion (2006–2014), a surge in publications (2015), continued growth up to 2022, and a recent decline in new research output from 2023 to 2024.Findings–The Journal of Transformative Education appears to be the most prolific outlet, whereas Streck, D.R., and Zembylas, M., are identified as the most central authors. The United States remains the leading contributor, with dominant keywords centered on education, social change, critical pedagogy, and sustainability.Contribution–The originality of this study lies in establishing the first bibliometric mapping of education and social transformation research, which contributes to conceptual clarity of this interdisciplinary field and provides strategic directions for future studies and policy development in transformative education.